Involving stakeholders in the commissioning and implementation of fishery science projects: experiences from the U.K. Fisheries Science Partnershipa. Issue 4 (12th August 2013) - Armstrong, M. J.; Payne, A. I. L.; Deas, B.; Catchpole, T. L.
<x xml:space="preserve">Abstract</x> Following from similar initiatives worldwide, the U.K.'s Fisheries Science Partnership (FSP) was established in 2003 to provide the fishing industry with opportunities to propose and participate in scientific studies in collaboration with fishery scientists. Key concepts were that most of the available funding would support industry participation, that industry, not scientists, would come up with the ideas for projects, and that commercial fishing vessels and fishing methods would be used to address specific concerns of the fishing industry in a scientifically controlled manner. Nearly 100 projects had been commissioned by March 2012, covering annual time‐series surveys of stocks subject to traditional assessment, and ad hoc projects on, e.g. gear selectivity, discard survival, tagging and migration and fishery development. The extent to which the results of the projects have been used by stakeholders, fishery scientists and fishery managers at a national and E.U. level is evaluated, along with the degree of industry interest and involvement, and reasons are identified for successes or failures in the uptake of the results into management and policy. Finally, the question is posed whether the programme has been successful in improving the engagement of the fishing community in the science–management process and in fostering communication and greater trust between fishers, scientists and managers.